If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -7) = 2(x + -0.5) Reorder the terms: 3(-7 + x) = 2(x + -0.5) (-7 * 3 + x * 3) = 2(x + -0.5) (-21 + 3x) = 2(x + -0.5) Reorder the terms: -21 + 3x = 2(-0.5 + x) -21 + 3x = (-0.5 * 2 + x * 2) -21 + 3x = (-1 + 2x) Solving -21 + 3x = -1 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -21 + 3x + -2x = -1 + 2x + -2x Combine like terms: 3x + -2x = 1x -21 + 1x = -1 + 2x + -2x Combine like terms: 2x + -2x = 0 -21 + 1x = -1 + 0 -21 + 1x = -1 Add '21' to each side of the equation. -21 + 21 + 1x = -1 + 21 Combine like terms: -21 + 21 = 0 0 + 1x = -1 + 21 1x = -1 + 21 Combine like terms: -1 + 21 = 20 1x = 20 Divide each side by '1'. x = 20 Simplifying x = 20
| 5+2x+6+2x=12x+30-7x-38 | | 20-3(7-6P)+9P= | | 2x+24x=180 | | 5(1.3-6.5x)-6(8.1x-4)=7.1x-12.3 | | 5-7x=45-14x | | 5x-4-6x=-10 | | 0.25(8k-4)=k+8-2k | | 8.1a+2.3=5.1a | | 30x+20=30 | | -1.20a=8 | | 8p-2=3p+6 | | -1.2a=8 | | 4x+7=25-2x | | (4x+2)-2(x+1)=12 | | b+6b=-16+3b | | -7+4x=-35 | | 0.72x-19.7=0.3(.2x+18) | | -2x+15=-35 | | -x+1+2x=2 | | 75.00+25x=162.5 | | 3x+27=54 | | 13d-25=3d | | -2c=-16 | | 2x-7=25-2x | | 8ln(11-6x)=4 | | 5x-9-x=7 | | x+5=9x-3 | | xa^2=c-b | | 5x-4+2x=2x+1 | | 6m+16=45x+18-13 | | 1.5h-5=1 | | 4x+31=12x-39 |